2019
DOI: 10.1080/0886022x.2019.1679644
|View full text |Cite
|
Sign up to set email alerts
|

Association of acute kidney injury with frailty in elderly population: a systematic review and meta-analysis

Abstract: Aim: The objective of this study was to assess whether an elderly patient’s frailty was associated with acute kidney injury (AKI) and to examine whether severe frailty group had an increased risk of AKI than mild–moderate group.Methods: We searched The Cochrane Library, PubMed, and EMBASE for relevant studies without language limitations before 1 March 2019 with a priori defined inclusion and exclusion criteria. Five population-based cohort studies were included for systematic review and meta-analysis.Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 32 publications
(43 reference statements)
3
29
0
1
Order By: Relevance
“…Huang, Fan, Ying, & Chen, 2019). As synonymous concepts of social participation can be used interchangeably, the search terms in this study were collected from previous systematic reviews or meta‐analyses to retrieve as many relevant resources as possible (Dalemans, de Witte, Lemmens, van den Heuvel, & Wade, 2008; Jiesisibieke et al, 2019; Shah, Frank, & Ehrlich, 2020). To further guarantee our reasonable selection of these terms and their relevant meanings, our team discussed them and invited suggestions from experienced specialists in the field of geriatric care and information specialists.…”
Section: Methodsmentioning
confidence: 99%
“…Huang, Fan, Ying, & Chen, 2019). As synonymous concepts of social participation can be used interchangeably, the search terms in this study were collected from previous systematic reviews or meta‐analyses to retrieve as many relevant resources as possible (Dalemans, de Witte, Lemmens, van den Heuvel, & Wade, 2008; Jiesisibieke et al, 2019; Shah, Frank, & Ehrlich, 2020). To further guarantee our reasonable selection of these terms and their relevant meanings, our team discussed them and invited suggestions from experienced specialists in the field of geriatric care and information specialists.…”
Section: Methodsmentioning
confidence: 99%
“…Usually the term ‘‘elderly’’ denotes broadly older individuals, but there is not universally accepted definition or cut-off age. Indeed, many authors have proposed various ages ranging from 60 years (indicated as elderly) to >80 years (indicated as very elderly) in the attempt to define the aged status [ 15 , 16 , 17 ]. Currently, it is reasonable to call “elderly” a patient with age >65 years.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, to mitigate the AKI risk level of an elderly patient, adequate enhancement of daily activities and nutrition might offer another type of treatment; those two criteria would improve an elderly patient's overall frailty. This finding is complementary to the result of [15]. Under certain controllable circumstances, elderly patients may improve their frailty before surgery that might cause AKI complications.…”
Section: Dematel-based Anp (Danp) Weightsmentioning
confidence: 64%